Minangkabau Customary Marriage Traditions: Integration of Custom and Sharia Principles in the Perspective of Islamic Law - Awis Alhkarni; Novia Yuriska (USRATY : Journal of Islamic Family Law, 2024)
This study examines the integration of Minangkabau customary marriage traditions and Islamic law, focusing on how both systems coexist and influence marital practices within the Minangkabau community. Minangkabau society is characterized by a unique matrilineal system, where family lineage and property are passed through the mother’s side, which sometimes conflicts with the patriarchal principles found in Islamic law. The research explores how religious leaders (ulama) and adat authorities navigate these differences, seeking a balance that respects both cultural traditions and Islamic teachings. By analyzing the roles of women, gender dynamics, and family responsibilities in Minangkabau marriages, the study assesses the impact of integrating these two legal systems on societal expectations, marital roles, and the protection of individual rights. Additionally, the study examines the social implications of combining adat and sharia, particularly in terms of gender equality, inheritance, and family leadership. The findings suggest that while challenges exist, the collaboration between Islamic and customary laws can lead to a more inclusive understanding of marriage, where both traditions are respected. This research provides recommendations for legal reforms, educational initiatives, and policy changes to facilitate a more harmonious integration of adat and sharia, while preserving the cultural heritage of the Minangkabau people.